A Report of Two Cases with Different Methods of Indexing for Orbital Prosthesis in Craniofacial Rehabilitation - Jain, Ajay; Ugrappa, Sridevi; Lan, See Gaik (Indonesia Prosthodontic Association, 2021)
Prosthetic rehabilitation of an orbital defect plays an important role in restoring the aesthetics of the face; therefore psychology, well-being and social acceptance of the patient in the society. The most difficult task in fabricating an orbital prosthesis is maintaining the position of the eye shell in the silicone without positional discrepancy during processing. This presentation will describe two simplified techniques for the rehabilitation of two patients with an orbital defect, using two different indexing methods to maintain the integrity of an artificial eye with the silicone. The case report one discusses the technique of hollow orbital prosthesis fabrication by indexing on the rear side of an artificial eye and case report two discusses the technique of solid orbital prosthesis fabrication by indexing on the front side of the artificial eye. The techniques presented in this presentation are easy to perform to fabricate hollow and solid orbital prosthesis whereby, the wholeness of silicone with the artificial eye is maintained by two different indexing methods. The technique described is a simple and easy way for the fabrication and rehabilitation of an orbital defect with hollow and solid orbital prosthesis using silicone, where retention is achieved by a combination of medical-grade adhesive and to a very small extent by bony and soft tissue undercut, hence providing a better aesthetic and psychological outcome.